The nutritive value of the proteins of fishmeal and peanut oilcake meal for growing swine - Van der Vyver, B. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1950.